E?cacy of Sertaconazole and Terbina?ne in Patients with Tinea Corporis and Tinea Cruris - Mayank Kaushik (Asian Journal of Medical Research, 2021)
Background: To assess efficacy of sertaconazole and terbinafine in patients with tinea corporis and tinea cruris. Subjects and Methods: Sixty- four patients with tinea corporis and tinea cruris of both genders were enrolled and were divided into 2 groups of 32 each. Group I were given sertaconazole (2%) twice daily and group II were given terbinafine (1%) twice daily. Response to treatment was assessed after 3 weeks. Results: Group I had 20 males and 12 females and group II had 18 males and 14 females. The mean value of scaling was 1.17 in group I and 1.14 in group The mean value of erythema was 1.46 in group I and 0.60 in group II. The mean value of pruritus was 1.37 in group I and 0.70 in group II. The difference was significant (P< 0.05). Response of treatment was poor seen in 24% in group I and 45% in group II. Moderate response was seen in 43% in group I, 40% in group II and good response was seen in 33% in group I, and 15% in group II. The difference was significant (P< 0.05). Conclusion: Sertaconazole was efficient in management of cases of tinea corporis and tinea cruris as compared to terbinafine.